Digital Maturity and the Stages of Digital Transformation in Culinary MSMEs in Indonesia - Priambada, Swasta (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Digital transformation is increasingly essential for the sustainability and competitiveness of micro, small, and medium enterprises (MSMEs), including the culinary subsector as a key pillar of Indonesia’s creative economy. However, digital adoption among culinary MSMEs remains fragmented and does not yet reflect comprehensive digital maturity. This article synthesizes the literature on digital maturity concepts, stages of digital transformation (digitisation–digitalisation–digital transformation), and the main barriers and contextual factors shaping digital maturity development in Indonesian culinary MSMEs. Using a narrative literature review, this study analyzes academic publications and institutional reports through thematic synthesis to identify key patterns and research gaps. The findings indicate that digital maturity is a gradual and multidimensional process encompassing strategy, operational processes, technology and data utilization, human resources and organizational culture, and customer management. Digital maturity advancement is constrained by structural barriers such as limited digital literacy, financing constraints, regulatory and infrastructure challenges, platform dependency, and geographical disparities. This article proposes a contextualized conceptual framework linking digital maturity stages with key enablers, barriers, and outcomes, contributing a context-sensitive perspective from a developing country and providing a foundation for future empirical research and MSME policy formulation.